Practical Common Lisp - Seibel, Peter (Apress, 2012)
If you think the greatest pleasure in programming comes from getting a lot done with code that simply and clearly expresses your intention, then programming in Common Lisp is likely to be about the most fun you can have with a computer. You’ll get more done, faster, using it than you would using pretty much any other language. That’s a bold claim. Can I justify it? Not in a just a few pages in this chapter—you’re going to have to learn some Lisp and see for yourself—thus the rest of this book. For now, let me start with some anecdotal evidence, the story of my own road to Lisp. Then, in the next section, I’ll explain the payoff I think you’ll get from learning Common Lisp.